Perhitungan Harga Pokok Produksi Untuk Penentuan Harga Jual Tenun Putri Mas di Desa Sebauk Kecamatan Bengkalis - Seli Tarisa Tamara; Nur Anita (SENTRI: Jurnal Riset Ilmiah, 2025)
This study aims to analyze the calculation of the Cost of Goods Manufactured (COGM) of Tenun Putri Mas, a traditional weaving enterprise located in Sebauk Village, Bengkalis District, and to determine the appropriate selling price using the full costing method. The research stems from the need for weaving-based MSMEs to implement accurate and comprehensive cost calculations, as the production of traditional woven fabrics involves significant expenses related to raw materials, direct labor, and manufacturing overhead. A descriptive quantitative approach was employed, with data collected through interviews, observations, and documentation during the production period of September–November 2025.The results show that the COGM calculated by Tenun Putri Mas amounts to Rp 35,482,500 per month with a production output of 120 pieces, resulting in a unit production cost of Rp 295,687. In contrast, the calculation using the full costing method produces a total manufacturing cost of Rp 42,061,674, resulting in a higher unit cost of Rp 350,513. The difference occurs because the full costing method incorporates all manufacturing overhead costs, including indirect labor and equipment depreciation, which were previously not included in the UMKM’s internal calculation. These findings indicate that using the full costing method provides a more accurate reflection of actual production expenses, allowing the business to determine a selling price that not only covers all costs but also supports optimal profit margins. The study recommends that Tenun Putri Mas adopt a more structured cost-recording system to enhance business sustainability, transparency, and competitiveness in the traditional weaving market.